Differentiation and characterization of human facial subcutaneous adipocytes - Chon, Su-Hyoun (Adipocyte, 2014)
Aging is associated with the loss of facial subcutaneous fat and with increased abdominal subcutaneous fat. Site specific differences in adipocyte phenotype and/or gene expression may play a role in these age-related changes. In this study, we isolated and characterized human facial preadipocytes and investigated distinct metabolic properties such as a differentiation pattern in relation to abdominal preadipocytes. Subcutaneous preadipocytes were isolated from human facial and abdominal skin and cultured in the presence of differentiation factors including rosiglitazone, a known peroxisome proliferator-activated receptor gamma (PPAR-γ) agonist, isobutyl-methyl xanthine (IBMX) and insulin. Differentiation was characterized microscopically and by quantitative real-time PCR. Unexpected superior adipogenic capacity of facial preadipocytes was observed; more facial preadipocytes differentiated in response to rosiglitazone than abdominal preadipocytes and facial preadipocytes retained their ability to differentiate through passage 11 compared with passage 5 for abdominal preadipocytes. Experiments confirmed a reduced lipolysis response in facial versus abdominal adipocytes after exposure to isoproterenol, which was consistent with the reduced β2-adrenergic receptor expression by 60% in the facial cells. The expression of other lipid metabolic gene markers was similar in both facial and abdominal adipocytes with the exception of β(3)-adrenergic receptor which was only found in abdominal adipose tissue. Gene profiling, by microarray analysis, identified that several HOX genes are robustly reduced in facial adipocytes compared to abdominal adipocytes, suggesting different characteristics between the 2 fat depots. These differences may have implications for development of treatments for facial fat loss during aging.